Envelhecimento populacional e reforma da política de aposentadoria no regime geral de previdência social - Diniz, Matheus Brito Nunes (2016)
Faced with the continuing decline in population work mass activity, in contrast to the growing number of retirees, the financial and actuarial balance of the entire system of public security is called into question, demanding measures to enable the rebalancing of this scale. The question becomes even more delicate by the political and ideological choice of the brazilian constituent legislator, which adopted a pay-as-you-go system of social security financing model, sustained by the principle of social solidarity and dependent on social contributions made by the economically active population to accomplish their commitments. Thus, the objective is to study some of the major legal reforms suggested within the retirement policy for age and contribution time now practiced by RGPS, especially because of Brazil's new age setting, whose population undergoes with a fast aging process. Through an essentially bibliographic research, there has been produced an analysis of the problems above, in attempt to highlight the main aspects that may lead to the affirmation of a social security currently lagging in structural terms. It is observed that, while a neuralgic public policy for the country, RGPS has not followed the national demographic dynamics. Facing that process undergoes, inevitably, by reviewing the rules of access to retirement by age and contribution time, that is, which is presented as a measure of adaptation of RGPS rules to the new characteristics of a people living longer and better. In addition to its perfect compatibility with the brazilian legal system, these changes also represent a rereading of the breakthrough concept of social protection, in which the tightening of the rules means, in Brazil and in other countries experiencing the same phenomenon, the preservation of pension system for future generations.